2009
DOI: 10.1177/003804070908200202
|View full text |Cite
|
Sign up to set email alerts
|

College Proximity: Mapping Access to Opportunity

Abstract: The process by which students decide whether and where to attend college has been based most commonly on a college-choice model that is independent of the students' geographic context. However, the ability to attend college close to home is often among the most important factors that U.S. high school students, especially minorities and the socioeconomically disadvantaged, consider. The study presented here mapped the place of residence of a national sample of high school seniors, as well as the location of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
225
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(248 citation statements)
references
References 29 publications
16
225
0
7
Order By: Relevance
“…The analyses presented here therefore underscore the complexity and diversity of the gendered patterns and predictors of college attendance, and suggest the need for more research on the potentially unique factors that may influence the paths to 2-year colleges. For example, recent work by Turley (2009) suggests that Hispanic youth's greater proximity to 2-year colleges rather than 4-year colleges in Texas and elsewhere is an important factor to consider when exploring differences in college trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses presented here therefore underscore the complexity and diversity of the gendered patterns and predictors of college attendance, and suggest the need for more research on the potentially unique factors that may influence the paths to 2-year colleges. For example, recent work by Turley (2009) suggests that Hispanic youth's greater proximity to 2-year colleges rather than 4-year colleges in Texas and elsewhere is an important factor to consider when exploring differences in college trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…Die unterschiedliche erreichbarkeit von Hochschulen tangiert aber auch die Frage der Chancengerechtigkeit (vgl. Turley 2009). Die geographische Dichte des Hochschulangebots und die Sensitivität der individuellen Nachfrage nach einem Studium in Abhängigkeit von der Distanz zwischen dem Wohnort und der nächstgelegenen Hochschule stellen daher für die Bildungspolitik wichtige größen dar.…”
Section: Introductionunclassified
“…bspw. Tinto 1973;McHugh und Morgan 1984;Sà et al 2004;Avery und Hoxby 2004;long 2004;Drewes und Michael 2006;Frenette 2006Frenette , 2009Turley 2009). Trotzdem ist nicht eindeutig klar, ob dieser Zusammenhang auch wirklich kausaler natur ist, denn die Schätzung der Korrelation könnte durch das Vorliegen von Endogenität verzerrt sein.…”
Section: Introductionunclassified
“…Spohn, Crowther, and Lykins (1992) found that rural isolation affected the educational attainment of Appalachian youth largely through institutional barriers (e.g., lack of information about financial details). Other research has found that geographic proximity to college increases the likelihood that students will apply to college (Turley, 2009), highlighting the importance of geography in college pursuit.…”
Section: Community Characteristicsmentioning
confidence: 99%